Characterizing Warm Temperature during April 2019 Monsoon Transition in the Central part of Java - Andung Bayu Sekaranom (Indonesian Journal of Geography, 2023)
Warmer temperature than normal has been observed in the central part of Java Island-Indonesia during the monsoon transition in 2019. To explain the environmental process related to temperature variability, this research aims to characterize the process related to temperature anomaly and explain the contributing factors in terms of radiation balance and latent heat flux. This research uses the data from two meteorological stations from the Indonesian Bureau of Meteorology, Climatology, and Geophysics (BMKG) and the National Centers for Environmental Prediction (NCEP/NCAR) Reanalysis Project to explain the temperature anomaly. Several parameters, such as near-surface air temperature and humidity, cloudiness, solar and longwave radiation, as well as latent heat flux are obtained from the reanalysis data. This study focuses on descriptive time-series data analysis to explain the factors that contribute to the April 2019 temperatures. The results of this study show the effect of the Madden–Jullian Oscillation (MJO) on weather anomalies. The increase in humidity when the study area is traversed by the MJO causes an increase in humidity followed by intensive cloud formation and the release of latent heat in the cloud. The release of latent heat contributes significantly to the increase in temperature compared to the effect of the shortwave and longwave radiation balance. Thus, atmospheric phenomena in the tropics need to be studied further concerning warmer temperatures because they can be significantly affected by climate change.